A Novel Icephobic Strategy: The Fabrication of Biomimetic Coupling Micropatterns of Superwetting Surface. Issue 19 (12th August 2019) - Li, Xinlin; Wang, Guoyong; Zhan, Bin; Li, Shuyi; Han, Zhiwu; Liu, Yan
Abstract: This work proposes a biphilic icephobic surface by combining the top‐down and bottom‐up methods. It is found that the impacting droplet on biphilic surface is divided into several parts during the recoiling process, which can significantly reduce the drop contact time before freezing. The anti‐icing test of the biphilic surface in the simulated environment also proves its excellent icephobic capacity. At one aspect, the freezing delay time on biphilic surface is positively correlated with the pillar diameters and negatively correlates with the distance of adjacent pillars. At another aspect, the stress concentrator at the edge between the superhydrophobic area and superhydrophilic area results in the dramatic reduction of ice adhesion strengths. In the real environment test, substantial particle ice is found on the biphilic surface. Different from the glaze ice and rime ice, the particle ice has a smaller contact area with the surface and is easier to be removed. Furthermore, the as‐prepared biphilic surface possesses good mechanical robustness and a long lifespan in the cyclic icing/melting test. It is shown that the new class of nonwetting surfaces presented here can be useful for anti/deicing applications in the future. Abstract : A biphilic icephobic surface is successfully fabricated by combining the top‐down and bottom‐up methods. The wettability shifting structure on the surface can greatly alter the dynamic mechanics of the impacting water droplets and cause the dramatic reduction of ice adhesion strengths, which shows great potential in anti/deicing applications in the future.